Potential retrofitting of UTM existing buildings to green building - Foo, Kian Seng (2011)
Green building is building that focuses on maximize the energy efficiency and resources used, while minimize building impact on human health and the environment during its life cycle. But previously, many building built is non-sustainable design and construction include UTM campus building. In Malaysia, existing buildings and its communities contribute over 40% of green house gases to the environment. Thus, there is potential retrofitting of existing buildings to green building. In order to achieve the above requirement, a rating system call Green Building Index (GBI) is used in Malaysia. The study is carried out in order to determine the potential of retrofitting the UTM existing buildings to green building. Although the establishment of GBI in the country had lead to the nation awareness on green building, but there is a need to figure out such awareness on UTM communites. Serious awareness on the UTM community will give more confidence to top management to consider the potential of retrofitting for existing building to green building. Besides, recent year top management of UTM had taken a big step in green by comprehensive initiatives towards sustainable campus by its sustainable campus policies. These comprehensive campus sustainable policies had rise up the potential retrofitting of UTM existing building to Green building. In additional to, UTM had set a target to reduce 10% energy used in campus in 2010. This is because high and increasing cost of campus utilities, operation and maintenance indicate that UTM is practicing unsustainable living conditions. The nature of green building which is energy efficiency becomes a critical need. Therefore it becomes a need to retrofit the existing building to green building.